THE EFFECT OF INTERNATIONAL FINANCIAL REPORTING STANDARDS ON THE FINANCIAL STATEMENTS OF AGRICULTURAL COMPANIES IN INDONESIA - Saif , Gehad Mohammed Sultan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study investigates the impact of the implementation of the Indonesian Financial Accounting Standards (SAK) on the financial performance of agricultural companies in Indonesia. The agricultural sector plays a vital role in the country's economy, and the adoption of SAK aims to improve financial reporting practices and enhance transparency. The research focuses on liquidity ratios, solvency ratios, and profitability ratios, specifically Return on Assets (ROA). A sample of agricultural companies listed on the Indonesia Stock Exchange from 2016 to 2019 was analyzed using descriptive statistics and hypothesis testing. The results indicate a significant difference in the profitability ratio after the implementation of SAK 69, suggesting that it has the potential to increase company profits. However, no significant differences were found in liquidity and solvency ratios. These findings provide valuable insights for policymakers in formulating accounting regulations that align with the needs of the agricultural sector.